A preparation method of a yttrium-zirconium-cerium ternary entropy oxide ceramic material
The microwave sintering technique was used to prepare yttrium-zirconium-cerium ternary medium-entropy oxide ceramic materials, which solved the problem of poor stability of CeO2-based composite ceramics. This technique enabled low-temperature rapid synthesis and efficient production, improving the stability and purity of the materials, making them suitable for automotive three-way catalysts and other extreme environment applications.
Patent Information
- Application Number
- CN202511881218.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-15
- Publication Date
- 2026-03-20
- Estimated Expiration
- 2045-12-15
AI Technical Summary
Existing technologies are insufficient to effectively improve the stability of CeO2-based composite ceramics. Traditional preparation methods suffer from high-temperature requirements, impurity introduction, equipment complexity, and environmental issues, which limit the application of medium-entropy oxides.
Yttrium-zirconium-cerium ternary medium-entropy oxide ceramic materials were prepared using microwave sintering technology. The high penetration capability of microwaves and the rapid sintering at low temperatures enabled uniform heating and efficient synthesis of the materials, avoiding crystal structure instability and impurity generation caused by high temperatures.
This study achieves high stability and reprocessability of yttrium-zirconium-cerium ternary medium-entropy oxide ceramic materials, reduces energy consumption, simplifies the preparation process, improves purity and production efficiency, and makes them suitable for industrial production.
Smart Images

Figure CN121318450B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of medium-entropy ceramic materials, and particularly relates to a preparation method of yttrium-zirconium-cerium ternary medium-entropy oxide ceramic material. BACKGROUND
[0002] CeO2ceramics are used as a cocatalyst or a catalyst carrier in automobile ternary catalysts due to good oxygen storage capacity. However, the reaction process involved in the above application is usually carried out at high temperature, and CeO2often causes volume fluctuation with the change of atmosphere, thereby seriously affecting the crystal structure and leading to poor stability, which affects the performance of the ceramic material used as a cocatalyst or a catalyst carrier. At present, the stability of CeO2-based composite ceramics is mainly realized by doping, but the doping content is usually small, and the improvement space for material stability is limited.
[0003] Medium-entropy oxides are a branch of high-entropy materials, and have good thermal stability and chemical stability, high hardness, unique electrical and magnetic properties, and wide application prospects in wear resistance, corrosion resistance, electromagnetic shielding, and ultra-high temperature extreme environments. Medium-entropy oxides are generally composed of 3-4 main elements in nearly equal proportions, between low-entropy and high-entropy materials, and have the advantages of traditional binary or simple multi-component oxides. The atomic arrangement and electronic structure are more complex, and can produce unique physical and chemical properties, that is, the high entropy value is used to greatly improve the stability of the material in extreme environments, and the specific performance of the material is not lost due to the reduction of the content of individual functional elements. For example, Zhao Ziqin et al. prepared a medium-entropy oxide functional filler containing Bi, Cd and Er elements by solution combustion method to achieve common shielding of low, medium and high energy γ-rays (Zhao Ziqin. Preparation and γ shielding performance of bismuth-cadmium-erbium medium-entropy oxide / epoxy resin composite materials[D]. Harbin: Harbin Institute of Technology, 2022). Wang Wenxue et al. found the mechanism of oxygen vacancy defects improving the near-infrared emissivity of corundum-type medium-entropy oxide ceramics and in-situ whisker growth phenomenon based on energy criterion and force stability criterion (Wang Wenxue. Preparation and microstructure regulation mechanism of corundum-type medium-entropy oxide ceramics[D]. Zhengzhou: Zhengzhou University, 2023).
[0004] Currently, the preparation methods of medium entropy oxides mainly include solid phase reaction method and precursor pyrolysis method. The traditional solid phase reaction method for preparing medium entropy oxides generally needs higher sintering temperature and longer holding time to ensure complete solid solution of each element, which is difficult to accurately grasp the reaction degree of raw materials, product type and proportion, and is easy to introduce impurities in the preparation process; the preparation of medium entropy oxides by precursor pyrolysis method needs more complex preparation equipment and more stringent preparation process, usually needs to use a large amount of organic matter or strong acid and strong base to adjust the precursor, which not only puts forward higher requirements for the preparation equipment, but also has low yield, and is easy to produce greenhouse gases or other harmful gases such as SO2 and HCl, and the product particles are difficult to sinter again, which limits the preparation and application of medium entropy oxides, therefore, based on the actual demand of medium entropy oxides, new preparation technology is urgently needed. SUMMARY
[0005] In order to solve the above technical problems, the yttrium-zirconium-cerium ternary medium entropy oxide (Y 1 / 3 Zr 1 / 3 Ce 1 / 3 )O2 ceramic powder material is prepared by microwave sintering technology, which has the characteristics of uniform heating, fast heating speed, low sintering temperature, short sintering time, less energy consumption and green and pollution-free by means of high penetration ability of microwave, so that the obtained yttrium-zirconium-cerium ternary medium entropy oxide ceramic material has good thermal stability and chemical stability.
[0006] In order to achieve the above purpose, the technical scheme adopted by the present application is as follows: a yttrium-zirconium-cerium ternary medium entropy oxide ceramic material, chemical formula is (Y 1 / 3 Zr 1 / 3 Ce 1 / 3 )O2, the crystal structure is face-centered cubic structure of cubic system, 225 Fm-3m space group, which is an equal proportion of single-phase oxide ceramic.
[0007] The preparation method of the yttrium-zirconium-cerium ternary medium entropy oxide ceramic material comprises the following steps:
[0008] Step one, mixing: Y2O3 powder, ZrO2 powder and CeO2 powder are weighed according to the molar ratio of 1:2:2, then ball-milled and mixed to obtain mixed powder;
[0009] Step two, pre-pressing blank: the mixed powder prepared in step one is dried and sieved, then placed in a cylindrical tabletting mold to obtain a circular blank; the drying treatment temperature is 40-80℃, and the time is 1-3h;
[0010] Step three, microwave sintering: the circular blank prepared in step two is microwave sintered, and the sintered sample is ground and sieved using a mortar to obtain yttrium-zirconium-cerium ternary medium entropy oxide ceramic powder.
[0011] Preferably, the Y2O3 powder has a purity of 99.99% and a particle size of 3-5 μm; the ZrO2 powder has a purity of 99.99% and a particle size of 0.5 μm; and the CeO2 powder has a purity of 99.99% and a particle size of 1-3 μm.
[0012] Preferably, the ball-milling mixing of step one is performed in anhydrous ethanol as the ball-milling medium, and the mass ratio of the anhydrous ethanol to the mixed raw materials is 1:1-3:1; and zirconia stabilizer is used as the grinding ball, and the mass ratio of the grinding ball to the mixed powder is 2:1.
[0013] Preferably, the ball-milling speed in the ball-milling mixing of step one is 300 r / min, and the ball-milling time is 6-24 h.
[0014] Preferably, the screen used in the sieving of step two is 100 mesh.
[0015] Preferably, the pressing condition of the tabletting in step two is: a pressing pressure of 19 MPa, a pressing time of 1 min, and a die diameter of 30 mm.
[0016] Preferably, the diameter of the round-shaped green body subjected to the pressing in step two is 30 mm, and the thickness is 2-5 mm.
[0017] Preferably, in the microwave sintering of step three, the pressed round-shaped green body is placed in an alumina crucible, and before the placement, a layer of alumina powder is uniformly laid on the bottom of the alumina crucible, and the thickness of the alumina powder layer is 1-2 mm.
[0018] Preferably, in the microwave sintering of step three, the sintering temperature is 1100-1400℃, the heating rate is 5-50℃ / min, and the holding time is 45-75 min.
[0019] Preferably, the screen used in the sieving of step three is 100 mesh.
[0020] The present application innovatively applies the microwave sintering technology to the synthesis of ternary entropy oxides, expands the synthesis method of ternary entropy oxides, and the obtained yttrium-zirconium-cerium ternary entropy oxide (Y 1 / 3 Zr 1 / 3 Ce 1 / 3)O2 ceramic material has good stability and reworkability; selecting microwave sintering can uniformly heat the material inside, avoid local temperature difference, make grain growth uniform, narrow particle size distribution and good dispersibility. At the same time, high heating rate sintering reduces the introduction of impurities and improves purity. Microwave sintering is a field-assisted sintering method, which uses the coupling effect of the special wave band of microwave and the microstructure of the material itself to make the microwave energy directly act on the material itself to heat the whole material to achieve the best sintering effect. It has the advantages of green energy saving in the sintering process, strong diffusion process, fast heating rate and high sintering efficiency. In addition, it can also inhibit the grain growth of the material and improve its mechanical properties. Because the microwave absorption capacity and microwave coupling method of different media are different, experiments need to be conducted to determine the appropriate microwave sintering parameters.
[0021] The present application uniformly lays a layer of alumina powder at the bottom of the alumina crucible, which can effectively prevent the chemical reaction between the circular blank and the crucible. The alumina powder laid at the bottom and the circular blank are not tightly connected, and the atomic spacing at the interface is much larger than the diffusion free path of atoms in solid phase reaction. In addition, the interface can reflect a part of the microwave to enter the blank again, reducing the microwave incident power of the bottom layer of alumina. Therefore, it is difficult for the blank and the alumina powder laid at the bottom to interdiffuse, preventing the circular blank and the crucible from sintering together.
[0022] The sintering temperature of the microwave sintering technology is low and the sintering time is short. The use of microwave reduces the activation energy of the material to accelerate sintering, shortens the sintering time and generates uniform fine grains. The small and round pores in the fine grains make the sintered material have good stability and reworkability. Under the action of microwave, atoms are activated to vibrate at a high frequency of billions of times per second. The mutual vibration and friction between atoms produce internal energy, which can effectively reduce the energy barrier of atomic diffusion, increase the activation energy of atoms, and make the whole material heat up to achieve the best sintering effect. At the same time, this interaction between microwave and raw materials also enables the present application to use micron-sized large-size raw materials for short-time solid phase reaction, which not only reduces the particle size requirement and price of raw materials, but also shortens the long-time sintering and energy waste caused by traditional heat conduction sintering method, and solves the problem of low raw material utilization rate caused by byproduct generation. In addition, under suitable impedance matching, microwave sintering technology can maximize the conversion of microwave energy to heat energy. Therefore, the present application only needs 0.6-3kW power to heat the blank to the sintering temperature, which is much lower than the common sintering power requirement of 5-12kW or more for ordinary sintering equipment.
[0023] Compared with high-entropy ceramics, the medium-entropy ceramics of the present application have a reduced number of components and a reduced configuration entropy, resulting in a weakened solid solution driving force between elements, especially for components with large differences in ionic radius (such as Ce 4The single-phase solid solution thereof is difficult to prepare. The essential difference causes the impedance matching requirement of the microwave field to be more stringent and the allowable error window of the process parameter to be narrower in the microwave synthesis process of the medium-entropy ceramic. In comparison, the multi-component characteristics of the high-entropy ceramic make it easier to achieve good microwave coupling. The microwave impedance matching of the medium-entropy ceramic is more difficult to achieve and the process fault tolerance is smaller than that of the high-entropy ceramic with more components. Therefore, the microwave synthesis of the medium-entropy ceramic faces a series of challenges such as difficulty in controlling phase purity, strong time-varying nature of dielectric properties, and high process sensitivity. In view of the problem, the application provides a precise microwave synthesis method, which optimizes the microwave sintering process, accurately controls the process parameters, reduces the reaction temperature, effectively inhibits the abnormal growth of grains, obtains submicron uniform grains, optimizes the microwave energy absorption and conversion efficiency, and effectively inhibits the generation of impurities, thereby solving the problems of uneven heating and reaction out of control caused by the dramatic change of dielectric properties during the synthesis of the medium-entropy ceramic.
[0024] The application has the advantages that: the raw materials are simple, the preparation steps are simple, and the production efficiency is high. The yttrium-zirconium-cerium ternary medium-entropy oxide ceramic powder is synthesized at low temperature and high efficiency by using the microwave sintering process. The sintering temperature is low and the sintering time is short by using the microwave sintering technology. The activation energy of the substance is reduced by using the microwave to accelerate sintering. The sintering time is short to generate uniform fine grains. The internal pores of the fine grains are small and round, which makes the sintering temperature low and the sintered material has good stability and reworkability. The process is easy to realize continuous production, further improves the production scale and efficiency, and provides a new way and idea for industrial microwave sintering preparation of medium-entropy oxide ceramic powder. BRIEF DESCRIPTION OF DRAWINGS
[0025] Figure 1 The XRD diffraction pattern of the yttrium-zirconium-cerium ternary medium-entropy oxide ceramic material prepared in the application examples 1-3 is shown in the figure;
[0026] Figure 2 The EDS spectrum of the yttrium-zirconium-cerium ternary medium-entropy oxide ceramic material prepared in the application example 1 is shown in the figure;
[0027] Figure 3 The SEM image and mappings of the yttrium-zirconium-cerium ternary medium-entropy oxide ceramic material prepared in the application example 1 are shown in the figure. DETAILED DESCRIPTION
[0028] In order for those skilled in the art to better understand the technical solutions of the application and implement them, the application will be further described below in conjunction with specific examples and drawings, but the examples are not limiting to the application.
[0029] It should be noted that, unless otherwise specified, the experimental methods described in the following examples are conventional methods; and the reagents and materials used, unless otherwise specified, are all commercially available. The Y₂O₃ powder used in the examples has a purity of 99.99% and a particle size of 3–5 μm; the ZrO₂ powder has a purity of 99.99% and a particle size of 0.5 μm; and the CeO₂ powder has a purity of 99.99% and a particle size of 1–3 μm.
[0030] Example 1:
[0031] A method for preparing yttrium-zirconium-cerium ternary medium-entropy oxide ceramic powder material includes the following steps:
[0032] Step 1: Mixing: Weigh Y2O3 powder, ZrO2 powder, and CeO2 powder in a molar ratio of 1:2:2 and mix them together. Use anhydrous ethanol as the ball milling medium, with a mass ratio of anhydrous ethanol to mixed raw materials of 2:1. Use stabilized zirconia as the grinding balls, with a ball-to-material ratio of 2:1. Set the ball milling speed to 300 r / min and the ball milling time to 6 h to obtain the mixed powder.
[0033] Step 2: Pre-pressing the preform: The ball-milled mixed powder slurry is thoroughly dried and passed through a 100-mesh sieve to prevent agglomeration. The drying temperature is 60℃ and the time is 2 hours. Subsequently, the obtained oxide mixed powder is compressed into tablets. The pressing conditions of the fully automatic tablet press are: pressure 19MPa, pressing time 1min, and die diameter 30mm. A circular preform with a diameter of 30mm and a thickness of 3mm is obtained.
[0034] Step 3: Microwave Sintering: Place the pressed medium-entropy oxide green body into an alumina crucible. Before placement, evenly spread a 2mm thick layer of alumina powder on the bottom of the alumina crucible. Then, place the alumina crucible containing the medium-entropy oxide green body into a microwave tube furnace. Set the heating rate to 20℃ / min and hold at 1300℃ for 60 minutes. Subsequently, allow it to cool naturally to room temperature. Grind the sintered product and sieve it through a 100-mesh sieve to obtain yttrium-zirconium-cerium ternary medium-entropy oxide ceramic material powder.
[0035] Depend on Figure 1 The full XRD spectrum of sample 1 and the magnified XRD diffraction pattern in the range of 2θ = 28 to 33° show that sample 1 is completely dissolved into a ternary medium-entropy oxide with an equimolar ratio of metal elements. Moreover, in the XRD diffraction pattern of sample 1, the diffraction peak intensities of the ternary medium-entropy oxide first decrease, then increase, and then decrease again.
[0036] Figure 2 The image shows the EDS spectrum of the yttrium-zirconium-cerium ternary medium-entropy oxide ceramic material prepared in Example 1.
[0037] Figure 3 The image shows the SEM images and mappings of the yttrium-zirconium-cerium ternary medium-entropy oxide ceramic material prepared in Example 1. As can be seen from the image, Y, Zr, Ce and O are uniformly dispersed in the image, and there are no obvious blocky particles, no obvious aggregation or segregation. These four elements show a uniform distribution trend at the same scale, indicating that Y, Zr, Ce and O are well dissolved together, proving that the material has been successfully medium-entropy.
[0038] Example 2:
[0039] A method for preparing yttrium-zirconium-cerium ternary medium-entropy oxide ceramic powder material includes the following steps:
[0040] Step 1: Mixing: Weigh Y2O3 powder, ZrO2 powder, and CeO2 powder in a molar ratio of 1:2:2 and mix them together. Use anhydrous ethanol as the ball milling medium, with a mass ratio of anhydrous ethanol to mixed raw materials of 1:1. Use stabilized zirconia as the grinding balls, with a ball-to-material ratio of 2:1. Set the ball milling speed to 300 r / min and the ball milling time to 6 h to obtain the mixed powder.
[0041] Step 2, Pre-pressing the preform: The ball-milled mixed powder slurry is thoroughly dried and passed through a 100-mesh sieve to prevent agglomeration. The drying temperature is 40℃ and the time is 3 hours. Subsequently, the obtained oxide mixed powder is pressed into tablets. The pressing conditions of the fully automatic tablet press are: pressure 19 MPa, pressing time 1 minute, and mold diameter 30 mm, to obtain a circular preform with a diameter of 30 mm and a thickness of 2 mm.
[0042] Step 3, Microwave Sintering: The pressed medium-entropy oxide green body is placed in an alumina crucible. Before placement, a 1.5mm thick layer of alumina powder is evenly spread at the bottom of the alumina crucible. The alumina crucible containing the medium-entropy oxide green body is then placed in a microwave tube furnace. The heating rate is set to 5℃ / min, and the temperature is held at 1100℃ for 75min. Subsequently, it is allowed to cool naturally to room temperature. The sintered product is then ground and sieved through a 100-mesh sieve to obtain yttrium-zirconium-cerium ternary medium-entropy oxide ceramic material powder.
[0043] Depend on Figure 1 The full XRD spectrum of sample 2 and the magnified XRD diffraction pattern in the range of 2θ = 28 to 33° show that sample 2 is completely dissolved into a ternary medium-entropy oxide with an equimolar ratio of metal elements. Moreover, in the XRD diffraction pattern of sample 2, the diffraction peak intensities of the ternary medium-entropy oxide first decrease, then increase, and then decrease again.
[0044] Example 3:
[0045] A preparation method of a yttrium-zirconium-cerium ternary entropy oxide ceramic powder material, comprising the following steps:
[0046] Step one, mixing: Y2O3 powder, ZrO2 powder and CeO2 powder are weighed according to a molar ratio of 1:2:2, and the three are mixed, anhydrous ethanol is used as a ball milling medium, the mass ratio of anhydrous ethanol to mixed raw materials is 3:1, zirconia is used as a grinding ball, the ball-to-material ratio is 2:1, the ball milling speed is set to 300 r / min, and the ball milling time is 6 h, to obtain a mixed powder;
[0047] Step two, pre-pressing: the mixed powder slurry after ball milling is fully dried, and the dried powder is prevented from agglomeration through a 100-mesh sieve, the drying treatment temperature is 80 DEG C, and the time is 1 h, then the obtained oxide mixed powder is pressed, the pressing conditions of the full-automatic tablet press are: the pressing intensity is 19 Mpa, the pressing time is 1 min, the die diameter is 30 mm, a circular green body with a diameter of 30 mm and a thickness of 5 mm is obtained;
[0048] Step three, microwave sintering: the pressed entropy oxide green body is placed in an alumina crucible, before being placed, a 1-mm-thick layer of alumina powder is uniformly laid on the bottom of the alumina crucible, then the alumina crucible containing the entropy oxide green body is placed in a microwave tube furnace, the heating rate is set to 50 DEG C / min, and the temperature is kept at 1400 DEG C for 45 min, then the temperature is naturally cooled to room temperature. The sintered product is ground and sieved through a 100-mesh sieve, and a yttrium-zirconium-cerium ternary entropy oxide ceramic material powder is obtained.
[0049] From Figure 1 It can be seen from the XRD full spectrum of sample 3 and the local enlarged view of the XRD diffraction spectrum in the range of 2 theta = 28-33 degrees that sample 3 is completely solid-soluted into a ternary entropy oxide with an equimolar metal element ratio, and the diffraction peak intensity of the ternary entropy oxide in the XRD diffraction spectrum of sample 3 is first reduced, then increased, and then reduced again.
[0050] The specific embodiments of the application are described in detail above in combination with the drawings and examples, but the protection scope of the application should not be limited thereto, the application is not limited to the above examples, and any changes made within the protection scope of the claims of the application are within the protection scope of the application.
Claims
1. A method for preparing a yttrium-zirconium-cerium ternary medium-entropy oxide ceramic material, characterized in that, Includes the following steps: Step 1: Mixing: Weigh out Y2O3 powder, ZrO2 powder and CeO2 powder in a molar ratio of 1:2:2, and then ball mill them together to obtain a mixed powder. Step 2, Pre-pressing the blank: After drying and sieving, the mixed powder obtained in Step 1 is placed in a cylindrical tableting mold for tableting to obtain a circular blank; the drying temperature is 40-80℃ and the time is 1-3h. Step 3, Microwave sintering: The circular green body obtained in step 2 is microwave sintered at a temperature of 1100-1400℃, a heating rate of 5-50℃ / min, and a holding time of 45-75min; the sintered sample is then ground and sieved using a mortar and pestle to obtain yttrium-zirconium-cerium ternary medium-entropy oxide ceramic powder. The chemical formula of the yttrium-zirconium-cerium ternary entropy oxide is (Y 1 / 3 Zr 1 / 3 Ce 1 / 3 O2 has a face-centered cubic crystal structure, space group 225 Fm-3m, and is a single-phase oxide ceramic with equal proportions.
2. The method for preparing a yttrium-zirconium-cerium ternary medium-entropy oxide ceramic material according to claim 1, characterized in that: The purity of Y2O3 powder is 99.99%, and the particle size is 3-5 μm; the purity of ZrO2 powder is 99.99%, and the particle size is 0.5 μm; the purity of CeO2 powder is 99.99%, and the particle size is 1-3 μm.
3. The method for preparing a yttrium-zirconium-cerium ternary medium-entropy oxide ceramic material according to claim 1, characterized in that: In step one, the ball milling and mixing process uses anhydrous ethanol as the milling medium, with a mass ratio of anhydrous ethanol to mixed raw materials of 1:1 to 3:1; stabilized zirconia is used as the milling ball, and the mass ratio of the milling ball to the mixed powder is 2:
1.
4. The method for preparing a yttrium-zirconium-cerium ternary medium-entropy oxide ceramic material according to claim 1, characterized in that: In step one, the ball milling speed is set to 300 r / min and the ball milling time is 6 to 24 h.
5. The method for preparing a yttrium-zirconium-cerium ternary medium-entropy oxide ceramic material according to claim 1, characterized in that: The sieve used for screening in step two is 100 mesh.
6. The method for preparing a yttrium-zirconium-cerium ternary medium-entropy oxide ceramic material according to claim 1, characterized in that: The pressing conditions for the tablets in step two are: pressure of 19MPa, pressing time of 1min, and mold diameter of 30mm.
7. The method for preparing a yttrium-zirconium-cerium ternary medium-entropy oxide ceramic material according to claim 1, characterized in that: The circular blank pressed in step two has a diameter of 30mm and a thickness of 2-5mm.
8. The method for preparing a yttrium-zirconium-cerium ternary medium-entropy oxide ceramic material according to claim 1, characterized in that: In step three, during microwave firing, the pressed circular blank is placed in an alumina crucible, and before placing it, a 1-2 mm thick layer of alumina powder is evenly spread on the bottom of the alumina crucible.
9. The method for preparing a yttrium-zirconium-cerium ternary medium-entropy oxide ceramic material according to claim 1, characterized in that: The sieve used for screening in step three is 100 mesh.
Citation Information
Patent Citations
Preparation method of novel fluorite type high-entropy oxide ceramic
CN120117899A
Rare earth zirconate medium-entropy thermal barrier coating ceramic material and preparation method thereof
CN120841951A